Invariant Investigation and Exact Solutions of Some Differential Equations with Conformable Derivatives - Aliyu, Aliyu Isa; İnç, Mustafa; Yusuf, Abdullahi; Bayram, Mustafa (Amer Scientific Publishers, 2018)
In this work, the conformable Harry-Dym, conformable logarithmic-KdV and conformable Zakharov-Ito equations are studied by using the invariant subspace method (ISM). The method determines an invariant subspace and construct the exact solutions of the partial differential equations (PDEs) by reducing them to ordinary differential equations (ODEs). As a result of the calculations, polynomial and trigonometric function solutions are derived. Ultimately, for illustrating the acquired results, some numerical simulations are performed.
Keywords: Invariant Subspace Method; Exact Solutions; Conformable Differential Equations